Programa de aquisição de alimentos (PAA): proposta de modelo de avaliação de satisfação (MAS) dos agricultores familiares sobre os aspectos operacionais e socioeconômicos - Nascimento, Daniel Teotonio do (2015)
The government introduced, in 2003, the Programa de Aquisição de Alimentos (PAA) (Food Acquisition Program), to facilitate the marketing of farming family food, even so, ensuring food security for certain groups. The PAA is considered an important national public policy for farming family, which is essential to check the satisfaction level of one of its main performer, the farmers, because they are the ones that initiate the entire PAA process. It was noticed that the assessment methodologies of the PAA, developed up to now, have specific directions, not including important operating and socioeconomic indicators of the PAA. Therefore, this paper aimed to develop a model for the evaluation of public policy (PAA), the mode Compra com doação simultânea (CDS) (Purchase with Simultaneous Donation), able to detect the degree of satisfaction of the farmers in relation to operational and socioeconomic aspects of the public program. The Modelo de Avaliação de Satisfação (MAS) (Satisfaction Evaluation Model) developed, had two purposes: a) to detect the grade of satisfaction of farmers about the PAA public policy; and b) to assess the grade of satisfaction of family farmers about the management of the cooperatives or associations with which they are affiliated. The research, in its purpose, was descriptive and explanatory, about the means, it was bibliographical, documentary, field and study case. To verify the applicability of the proposed methodology, the Model MAS was tested in the Cooperativa da Agricultura Familiar e Solidária do Oeste do Paraná (COAFASO) (Cooperative of Agriculture Family and Solidarity of Western Paraná State). Data were tabulated and analyzed according to the steps set out in the Model MAS, using statistical techniques of exploratory analysis and dimensional analysis. After executing all the steps, it was verified the viability of the proposed Model, as it was possible to detect, in an objective way, the satisfaction level of the family farmers. The results showed that the farmers are satisfied about the PAA and the COAFASO Cooperative management. However, a number of producers showed dissatisfaction with some of the PAA indicators, especially about the prices paid for their products and for the required documents in relation some priority groups. About the Cooperative Management also were found some negative indicators. Thus, there were made two proposals of intervention. One targeted to the public agencies and other to the directors of COAFASO